Risk factors of neuropathic pain in multiple sclerosis: a retrospective case-cohort study - Ouyang, Huiying; Li, Xiaojun; Xu, Haoyou; Zhan, Yibo; Zheng, Zequan; Chen, Guixian; Lou, Zhenzhen; Chen, Haoxuan; Zhang, Jiahui; Mao, Hui; Zhang, Changlin; Qin, Lulu; et al. (Frontiers in Immunology, 2024)
Abstract Background Pain is a common symptom in multiple sclerosis (MS), especially neuropathic pain, which has a significant impact on patients’ mental and physical health and quality of life. However, risk factors that related to neuropathic pain, still remain unclear. Objective The study aimed to explore the risk factors of neuropathic pain among MS patients. Materials and Methods This retrospective study examined the consecutive patients diagnosed with MS in the Department of Neurology of Guangdong Provincial Hospital of Chinese Medicine between August 2011 and October 2022. Neuropathic pain was defined as “pain arising as a direct consequence of a lesion or disease affecting the somatosensory system”. Demographic and clinical features were obtained from the electronic system of the hospital. Results Our cohort revealed that the prevalence of patients with neuropathic pain in MS was 34.1%. The results indicated that the longer the spinal lesions, the greater the neuropathic pain risks (2-4: OR, 13.3(2.1-82), >5: OR, 15.2(2.7-86.8), p for tread: 0.037). Meanwhile, multivariate regression analysis showed that cervical and thoracic lesions (OR 4.276, 95% CI 1.366-13.382, P = 0.013), upper thoracic lesions (T1-T6) (OR 3.047, 95% CI 1.018-9.124, P = 0.046) were positively correlated with neuropathic pain, while basal ganglia lesions (OR 0.188, 95% CI 0.044-0.809, P = 0.025) were negatively correlated with neuropathic pain among MS patients. Conclusion Extended spinal lesions (≥3 spinal lesions), cervical and thoracic lesions, upper thoracic lesions were independent risk factors of neuropathic pain among MS patients. Furthermore, our study found that the longer the spinal lesions, the greater the neuropathic pain risks.